The Influence of Active Lifestyle, Physical Fitness, and Psychological Aspect to the Work Productivity at Polytechnic (Department of Physical Education, Sport, Health and Recreation, 2019)
The purpose of the study is to reveal the effect of physical fitness, psychological aspects, and active lifestyles on work productivity. The research uses descriptive methods. Through the purposive sampling method, it is obtained samples of 123 students. The instruments used are the self-evaluation format, physical fitness test, psychological test results, and semester report scores. The statistical approach used is multiple regression analysis. Based on data processing the results are as follows: The effect of an active lifestyle on work productivity of 0.0108% shows a very low influence, the effect of physical fitness on work productivity of 19.3% shows the influence on the low category, and the influence of psychological aspects on work productivity of 0.408% shows a very low influence. This study shows that there is no significant relationship between active lifestyle, psychological aspect, and work productivity, and there is a significant relationship between physical fitness and work productivity. The recommendation of this study is that Polman should pay attention to the level of physical fitness of its students in the process of completing academic programs in Polman.